Determining factors of flag football sport intention: bibliometric and mixed methods explorations - Gunawan, William Ben; Setyani, Angelica Herdyandra; Diptawibowo, Narendra Diwangkara; Perwitasari, Ghazlina Putri (Sriwijaya Journal of Sport, 2026)
Research Problems: Existing research on sports participation has predominantly examined general determinants of sports interest or intention to participate. However, interest or intention to participate in flag football, a growing yet less mainstream sport in Indonesia, remains understudied. Research Objectives: This study explores the underlying factors influencing individuals’ intention to participate in flag football, a rapidly growing sport known for its inclusivity and unique gameplay. Methods: The research was performed using combined approaches: the item was formulated through a bibliometric review and structured questionnaires from the results of interviewing 65 participants (qualitative approach), resulting in 26 items. As for the quantitative approach, the Kaiser-Meyer-Olkin measure of sampling adequacy and Bartlett’s Test of Sphericity confirmed 20 items suitable for factor analysis. The analysis revealed seven interpretable factors: Accessibility and Environmental Support, Personal Image and External Influence, Prior Sport Experience and Alternatives, Emotional and Novelty Aspects, Social Motivation and Self-Affirmation, Cognitive Stimulation and Excitement, and Competitive and Value-Based Orientation. These factors cumulatively explained 67.58% of the Intention to participate in flag football. Results: The findings suggest that both internal drivers (e.g., curiosity, mental stimulation) and external influences (e.g., facilities, media exposure) play significant roles in shaping interest toward sport. Implications of the findings span across different stakeholders, offering strategic insights for sports marketers, policymakers, educators, and community organizers to enhance participation rates and tailor flag football programs to diverse audiences. The study contributes to a more comprehensive understanding of sport engagement psychology and offers recommendations for future research in emerging sports adoption. Conclusion: The analysis resulted in the identification of seven distinct factors, each of which represents a unique dimension that shapes how individuals perceive and are motivated toward participating in flag football, reflecting both personal and contextual elements. The findings provide a comprehensive view of how various psychological, social, and environmental components interplay to influence sport adoption.